KORELASI KADAR DDIMER DENGAN JUMLAH SINUS VENA SEREBRAL PADA PASIEN CEREBRAL VENOUS THROMBOSIS - Aditya Kurnianto,* Yovita Andhitara,* Dodik Tugasworo,* Retnaningsih,*Rahmi Ardhini,* Vivi Kristiani (Neurona Majalah Kedokteran Neuro Sains, 2020)
INTRODUCTION CEREBRAL VENOUS THROMBOSIS CVT IS A RARE YET POTENTIALLY DEVASTATING DISEASE ACCORDING TO THE VIRCHOW TRIAD ONE OF THE PREDISPOSING FACTORS IS THE HYPERCOAGULABLE STATE OF THE BLOOD THAT CAN BE MEASURED WITH DDIMER